Interpreting students' ideas on the availability of energy and matter in food webs. Issue 1 (1st January 2023) - Wennersten, Lena; Wanselin, Hanna; Wikman, Susanne; Lindahl, Mats
ABSTRACT: UNESCO has identified education for sustainable development (ESD) as a key factor in the achievement of sustainable development goals (SDGs). Education is important in developing awareness of how to preserve natural ecosystems and promote the uptake of renewable energy sources. Ecology education in primary school aims to give students a scientific foundation to further their education in biology and develop environmentally literate citizens who will protect, restore and promote the sustainable use of natural ecosystems. This early education includes awareness of how human welfare depends on resilient ecosystems. However, previous studies have shown that young students face serious challenges when constructing a holistic view of ecological relationships. In this study, we interpret students' written texts and drawings on processes in an ecosystem. By focusing on students' expressed ideas on the availability of energy and matter in the ecosystem, we construe four models. The students in our study propose, firstly, that energy flows or can circulate, and secondly, that matter circulates, is provided by the sun, or is created anew. The students often express fragmented processes, combined in different ways. According to our results, we propose aspects that can inform the design of primary school teaching of ecology for sustainable development.